Refletindo sobre saúde indígena a partir da Opy (casa de reza) Guarani Mbya: uma análise centrada na experiência com os moradores da aldeia Tenondé Porã, município de São Paulo - Clemente, Giomar Henrique (2024)
The present work is about care and health promotion practices in the house called Opy (prayer house) Guarani Mbya, located in the indigenous village Tenondé Porã, district of Parelheiros, south zone of the municipality of São Paulo, in Brazil. In the universe of Guarani people, villages are born and organized from the opy (prayer house), a place used for meetings, celebrations, rituals, ceremonies and workshops. That place becomes a vital element for the existence of the Guarani community. This research is a qualitative study, based on the theory of decoloniality approach. It uses ethnography (critical ethnography) as its methodology, adopting participant observation as a means of being in the field research and configuring itself as participatory research. The study was made in two crucial moments: 1- the bibliographical research; 2- the field research in the indigenous village (tekoa) Tenondé Porã, exploring specially the opy (prayer house), as a central environment for indigenous health care. The approach dialogues with authors who discuss health, mental health, epistemology and decolonization, since the understanding of health in indigenous cosmology differs from the non-indigenous or Western society. In the indigenous Guarani Mbya context, health is built from nhandereko, understood as the Guarani way of life. Nhandereko covers aspects of time (ara pyau and ara yma), the organization system, the traditional agriculture, ceremonies, the tradicional blessings, language, relationships, building in reality a tekoa, understood as place or environment where the tekó (life) can be nurtured and reproduc